FORMULASI DAN UJI STABILITAS FISIK SEDIAAN MASKER WAJAH GEL PEEL-OFF EKSTRAK KULIT BUAH NAGA MERAH (Hylocereus polyrhizus) - Aditama, Agnis Pondineka Ria; Kusumaningtyas, Rili; Karimah, Widya Nuratika; Paramita, Denok Risky Ayu; Rashati, Dewi; Muslikh, Faisal Akhmal (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2024)
Red dragon fruit (Hylocereus polyrhizus) has many benefits. The fruit peel is rich in antioxidants which have the potential to improve the health and beauty of facial skin. Traditional use requires a long preparation time and formulation is needed to make preparations with more effective, practical and long-lasting storage. The facial mask formulation is a peel-off gel preparation that can moisturize the skin and increase the effect of the active ingredients. Quality assurance, namely safety, quality and benefits, is very necessary, which can be done by testing the physical stability of the preparation. The aim of this research is to obtain a formula made from the active ingredient Hylocereus polyrhizus fruit peel extract in the form of a peel-off gel facial mask and the best physical stability. HPMC was used as a carrier base by varying the concentration, namely 2%; 3% and 5%. Evaluation of the physical stability of the preparation was carried out, namely homogeneity, organoleptic, spreadability, viscosity, pH and dry time tests of 14 and 28 days. Storage is carried out at warm (30-40°C), room (15-30°C), and cold (2-8°C) temperatures. The best formula is 3% HPMC concentration with the best physical stability. Variations in storage temperature have an effect on physical organoleptics (color), viscosity and dispersion, but have no effect on physical homogeneity, drying time and pH. Cold temperatures (2-8°C) show the best stability because they can maintain physical stability.